Implementasi Teknologi Ozon Untuk Meningkatkan Lama Waktu Simpan Ikan Kembung Di Desa Air Genting - Dian Puspitasari; Intan Zahar; Endriyaman Zai; Riusman Hura; Riska Hariyani (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Mackerel (Rastrelliger sp.) is a type of marine fish widely consumed. Several factors influencing it include affordable prices, delicious taste, and the ability to be processed into various dishes. However, mackerel fish has a weakness: it quickly declines in quality if not managed properly. In the face of increasing demand, it is crucial to meet the need for fish with an optimal level of freshness. Methods have been used to maintain the freshness of fish, such as salting, freezing, and using plant ingredients. However, the use of natural ingredients from plants often has a low shelf life and can cause a decrease in fish quality. The method used in community service activities in Air Genting village is counselling. Counselling is carried out through the delivery of material, discussions (in the form of questions and answers), and explanations about tools capable of producing ozone. This activity aims to inform the public about technology with the ozone system. This technology can increase the shelf life of mackerel and keep the quality of the fish good and still suitable for consumption.            Keywords: fish; curing; ozone